Influence of Synthetic Plant Growth Stimulant, Miraculan on the Survival and Development of Spodoptera litura (fab.) (Lepidoptera: Noctuidae) - Bhatnagar, Shiwani; Kumar, Arvind; Karnatak, A. K. (Indian Forester, 2012)
Plant growth stimulants ’Miraculan’ gradually decreased survival of the larvae of Spodoptera litura from 86.67 to 46.67 per cent at 3.22 to 100 ppm. Similar trend was also observed in adult emergence. Growth indices were lower in all treated diets as compared to control. The results of the experiment showed that artificial diet fortified with different levels of Miraculan (plant growth stimulant) has adverse effect on the survival and development of Spodoptera litura. Reduction in per cent pupation, adult emergence and larval survival of S.litura indicates the role for these growth regulators in IPM.